Neural electrical dynamics during head down tilt and mental load - (:unkn) unknown (International Astronautical Federation, IAF, 2018)
Head down tilt (HDT) has been used as a ground-based analog for simulation of acute circulatory effects of microgravity on the central nervous system. Changes in cerebral hemodynamics elicited by HDT may impact neural activity and related cognitive processing. The aim of this study was to investigate the effect of HDT on neural electrical activity during i) the resting and ii) the increased mental workload state. The electroencephalogram (EEG) was recorded from 10 volunteers using 16 electrodes in two postural conditions (supine and HDT at -20o in random order) and during three tasks: Resting with eyes opened, resting with eyes closed, and then during mental load (backward serial subtraction with eyes closed). Each task lasted for two minutes. The power spectrum of the EEG was computed in the conventional frequency bands for frontal, occipital, parietal, midline, left and right electrode groupings. Separate ANOVA analysis was performed for each frequency band for electrode group x task x condition (the significance level was adjusted by Bonferroni correction). During HDT delta band power was found to be greater than during the supine condition (p<0.05). Frontal delta band power increased during the eyes opened task when compared with the eyes closed and the serial subtraction task (p<0.05). The theta band power of the supine condition was found to be higher than its corresponding value of HDT (p<0.01). Topographical changes of alpha band power were observed in the occipital and parietal exerting increments during the eyes closed task when compared to eyes opened and mental workload task (p<0.01). Frontal beta and gamma band power was found to increase during the mental workload task only for the supine condition (p<0.05). The mental workload task was not able to increase the spectral power of the beta and gamma bands during HDT. This decrement in neural synchronization in the frontal lobe may be related to the decrease in cerebral blood flow which has been reported as an acute response to HDT. Moreover, single epoch power values of the electrodes were used to estimate the posture via Multi-layer perceptron classifier. Supine position tasks were classified with an accuracy higher than 80 % where it was higher than 60% for the head down conditions. Copyright © 2018 by the International Astronautical Federation (IAF). All rights reserved.
Keywords: EEG; Head down tilt; Mental workload